БАСТАУЫШ СЫНЫП ОҚУШЫЛАРДЫҢ БАЙЛАНЫСТЫРЫП СӨЙЛЕУЛЕРІН МАЗМҰНДАМА ЖАЗДЫРУ БАРЫСЫНДА ДАМЫТУ ƏДІСТЕРІ - Бисембаева, Ж.К.; Оспаналиева, У.О. (My University, 2019)
Аннотация Бастауыш сынып оқушыларының байланыстырып сөйлеуді дамытудың тиімді əдіс-тə- сілдері, түрлері мен құралдары қарастырылған. Abstract In this article one of the actual and meeting modern requirements of problems becomes stu- dying of coherent speech, search of the corresponding ways and receptions, forms and means of development of speech activity at children.
Methods of development of coherent speech of pupils of initial classes in the presentation summaries
Keywords: мазмұндама; əдістер; құралдар; байланыстырып сөйлеу; composition; methods; means; coherent speech